Rapid and specific detection of Helicobacter pylori macrolide resistance in gastric tissue by fluorescent in situ hybridisation. Issue 5 (1st May 2000) - Trebesius, K; Panthel, K; Strobel, S; Vogt, K; Faller, G; Kirchner, T; Kist, M; Heesemann, J; Haas, R
Abstract : BACKGROUND: The development of macrolide resistance in Helicobacter pylori is considered an essential reason for failure of antibiotic eradication therapies. The predominant mechanism of resistance to macrolides, particularly clarithromycin, is based on three defined mutations within 23S rRNA, resulting in decreased binding of the antibiotic to the bacterial ribosome. AIM: To develop an rRNA based whole cell hybridisation method to detect Helicobacter species in situ within gastric tissue, simultaneously with its clarithromycin resistance genotype. METHODS: A set of fluorescent labelled oligonucleotide probes was developed, binding either to H pylori 16S rRNA or 23S rRNA sequences containing specific point mutations responsible for clarithromycin resistance. After hybridisation and stringent washing procedures, labelling of intact single bacteria was monitored by fluorescence microscopy. The new approach was compared with PCR based assays, histology, and microbiological culture. RESULTS: In comparison with the phenotypic resistance measurement by E test, the genotypic clarithromycin resistance correlated perfectly (100%) for 35 H pylori isolates analysed. In a set of gastric biopsy specimens (27) H pylori infection was confirmed by histology (17/27) and correctly detected by whole cell hybridisation. Five clarithromycin resistant strains were identified in gastric tissue specimens directly. Furthermore, non-cultivable coccoid forms of H pylori were easily detectable by whole cell hybridisation. CONCLUSIONS: Whole cell hybridisation of rRNA holds great promise for cultivation independent, reliable, and rapid (three hours) genotypic determination of clarithromycin resistance in H pylori . Compared with PCR techniques it is independent of nucleic acid preparations, not prone to inhibition, and allows semiquantitative visualisation of the bacteria within intact tissue samples.